(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with the issues of forming the historical novels in the USA literature. The author of the given article presents his opinion on the views of different scientists, where the irrelevance to the reality is shown by one-sided analyses of the facts. The role of such genres as memoirs, reminiescences and diaries in forming of the literature of USA is shown; while the XIX century is defined as the period of forming the historical novels.